A Conceptual Framework on The Successful Adoption of Project Management Methodologies in Ghana - Taana, Ivy Hawah (Technium Social Sciences Journal, 2020)
The successful completion of every project whether undertaken by a public or private organization is of primary concern to many institutions. However, literature has confirmed that most project success depends on adhering to good practices and are keenly documented in Project Management Methodologies (PMMs). It is a fact that many projects do not see successful completion as most of them are long overdue, faced with budget overruns and even some are abandoned. The purpose of this study is to explore the factors that influence the Adoption of Project Management Methodology in Ghana. This is motivated by the dearth of academic literature concerning the successful adoption of Project Management Methodologies in Ghana. The study will also examine if the Adoption of Project Management Methodologies leads to project success. To achieve these aims, a conceptual framework was developed grounded on the Critical Success Factors (CSFs), the Capability Maturity Model (CMM) theory, and the Stakeholder theory. Four independent variables, a mediator and a moderator were hypothesized for the establishment of the success factors affecting Project Management Methodologies adoption and if the Project Management Methodology adoption leads to project success.